Early Childhood Facility Staff Knowledge and Confidence with Food Allergy Management: A Preliminary Study. Issue 1 (March 2013) - Mullan, Judy; Rich, Warren; Kreis, Irene; Fleming, Catharine
THIS PRELIMINARY STUDY INVESTIGATED the level of staff knowledge and confidence in food allergy management in a group of NSW regional Australian early childhood facilities (ECFs) in 2007. A mixed-method design including both quantitative and qualitative approaches was used to identify staff knowledge and confidence in food allergy management. Quantitative data was analysed using descriptive statistics, while qualitative data was analysed thematically. Quantitative data revealed that knowledge and confidence about food allergy management varied considerably among the staff. Qualitative data revealed that, even though many ECF staff were knowledgeable about food allergy management, they lacked the confidence to deal with emergency situations. This study highlights that ECF staff knowledge and confidence when dealing with children who experience food-induced allergies is relatively poor, placing these children at risk of receiving suboptimal care. It is important therefore, to ensure that staff are both competent and confident in the management of food allergies in light of the introduction of the National Quality Framework in 2012.